IMPLEMENTASI PENDIDIKAN AKHLAK DALAM PEMBENTUKAN KARAKTER DI PONDOK PESANTREN AN NUUR KEMBANGBAHU - Chusnina Fithrotin Nada; Muhammad Asrori; Dita Miranda; Efika Dwi Cahyani; Firda Qurotul Aini; Khofifah Martha Noer; Nur Lailatul Isnaini; Tri Aliah Nur Ambarwati (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Abstract. Moral education is an important foundation in shaping the character of the younger generation,especially in an Islamic boarding school environment which has the main mission of producing individuals withnoble character. This study aims to analyze the implementation of moral education in shaping the character ofstudents at An Nuur Kembangbahu Islamic Boarding School. The method used is descriptive qualitative with datacollection techniques through observation, interviews, and documentation. The results showed that moraleducation at An Nuur Islamic Boarding School is implemented through a holistic approach that includeshabituation of good behavior, teaching Islamic values, and exemplary behavior from caregivers. Santri aretrained to apply moral values through activities such as congregational prayer, yellow book recitation, communityservice, and fostering social attitudes in everyday life. Strengthening Islamic values is carried out in an integratedmanner through the formal and non-formal curriculum. In addition, the ustadz and caregivers act as role modelswho consistently show commendable behavior, thus providing a positive influence on students. Thisimplementation has proven effective in shaping the character of students who are disciplined, responsible, honest,and have integrity. The results also revealed that the success of moral education at An Nuur Islamic BoardingSchool is inseparable from a supportive environment, and the commitment of caregivers in assisting students.This research confirms that moral education in pesantren is a strategic model in producing morally, intellectually,and spiritually superior generations.